Increased Visual Attentional Demands Alter Lower Extremity Sidestep Cutting Kinematics in Male Basketball Players - Koen T.H. Rikken; Tom Panneman; Fabian Vercauteren; Alli Gokeler; Anne Benjaminse (International Journal of Sports Physical Therapy)
# Background